Impacts of sleep disturbance and work-related life stress on depression among Japanese and Chinese workers. - Eiko Matsuda; Mariko Kikutani (PLoS ONE)
The present study investigated how life stress and sleep disturbance impact depressive symptoms among Chinese (N = 185) and Japanese (N = 464) workers. Based on a hypothesis that sleep disturbance can cause depression, a statistical model is established, expecting that work-related life stress indirectly increases depressive symptoms by worsening sleep disturbance rather than initiating depression directly. The study also examined the buffering effects of social support on depression. The extent of depressive symptoms, sleep disturbance symptoms (insomnia, hypersomnia, and nightmare), work-related stressors, and available social support were measured. The result revealed that the extent of depression was equivalent for both groups, but the Chinese reported more stress, less social support, and more severe sleep disturbance symptoms than the Japanese. Despite those differences, the statistical model fitted both groups well, suggesting that addressing sleep disturbance at the earliest opportunity can effectively prevent depression onset for workers.